(untitled) (Indian Journal of Public Health Research & Development, 2020)
In a series of five articles we put forth and establish a new principle, namely the cancer principle which we propose as a fundamental principle of nature. Cancer is an agent of the principle of disorder and is at the root of origin of life, evolution of species and may be, is also the determinant of the ultimate fate of all life. We introduce and motivate this principle and provide arguments in favor of its being at the origin of all evolution. Cancer is defined as the tendency for unrestrained proliferation that is operative in both inanimate and animate worlds and that has given rise to the phenomenon of life from the nonliving background.